Jinkui Shenqi Pill accelerates osteoporotic fracture healing by promoting bone formation through neurosensory PGE2/EP4/p-CREB axis - Jihao Xi; Jihao Xi; Danqing Fu; Danqing Fu; Dan Xu; Ruhan Shen; Ruhan Shen; Yan Zhao; Haoqiang Dai; Haoqiang Dai; Chenjie Xia; Chenjie Xia; et al. (Frontiers in Endocrinology, 2025)
PurposeJinkui Shenqi Pill (JKSQP), a traditional Chinese herbal formula, is clinically utilized in China for managing bone disorders secondary to kidney deficiency, including osteoporotic fractures (OPFs). The present study aims to elucidate the pharmacological mechanism underlying JKSQP’s therapeutic effects on OPF healing.MethodsLC-MS/MS was employed to characterize the chemical constituents of JKSQP. Two-month-old female C57BL/6J mice underwent bilateral ovariectomy (OVX) followed by transverse tibial osteotomy to establish the OPF model. These OPF mice were randomly divided into the JKSQP group and OPF group, in which mice were gavaged with 1 g/kg/day JKSQP and equivalent volume of normal saline, respectively. At 4, 14, and 24 days post-fracture, biological specimens including serum, tibiae, dorsal root ganglion (DRG) and hypothalamus were collected for ELISA assay, μCT analysis and histopathology staining. Primary bone marrow stromal cells (BMSCs) were treated with the serum obtained from Sprague-Dawley rats administered with 1.5 g/kg/day JKSQP via oral gavage for three consecutive days. The conditioned medium derived from these JKSQP serum-treated BMSCs and the serum collected from the JKSQP-treated mice were applied to the DRG neurons. The levels of COX-2, PGE2, EP4 and CGRP in vitro were detected using qRT-PCR, western blot, ELISA and immunofluorescence (IF).ResultsLC-MS/MS analysis identified 1872 chemical components in JKSQP. μCT evaluation demonstrated accelerated healing of OPF in JKSQP-treated mice. Histomorphometric analysis combined with Calcein double-labeling revealed enhanced bone formation within the fracture callus. Compared with OPF controls, mice in the JKSQP group exhibited elevated serum PGE2 levels, upregulated Osterix, COX-2 and EP4 expression in fracture callus, increased EP4 and CGRP in DRG, and enhanced p-CREB in hypothalamus. In vitro, JKSQP-containing serum increased both PGE2 secretion and COX-2 expression in BMSCs. Furthermore, qRT-PCR and IF analyses confirmed that both conditioned medium from JKSQP-treated BMSCs and serum from JKSQP-administered mice upregulated EP4 and CGRP expressions in DRG neurons.ConclusionJinkui Shenqi Pill accelerates OPF healing by promoting bone formation possibly through activation of neurosensory PGE2/EP4/p-CREB axis.